Psychological capital as a moderator between personality traits and flourishing in the sample of Lithuanian employees - Aiste Dirzyte; Kornelija Dovydaitytė; Aleksandras Patapas; Zilvinas Zidonis (Problems and Perspectives in Management)
Recent scholarly works in the field of organizational behavior highlight the critical importance of understanding the variables that contribute to employee flourishing. However, these variables are still under-researched while this information can contribute to the improvement of management practices. The purpose of this study was to explore the role of psychological capital as a moderator between personality traits and flourishing. The sample consisted of employees (n = 155) working full-time in various Lithuanian private organizations. The data were collected online through professional networks. Participants completed measures assessing the Big Five personality traits (BFI-2), psychological capital (self-efficacy, hope, optimism, resilience) (PCQ-24), and flourishing (FS). Correlation, multiple regression, and moderation analyses were conducted. Results demonstrated that extraversion, agreeableness, conscientiousness, and openness were positively associated with flourishing, whereas neuroticism was negatively associated. Together, these traits explained 68.5% of the variance in flourishing. Examining psychological capital, extraversion, agreeableness, and openness emerged as positive predictors, while neuroticism was a negative predictor, accounting for 47.9% of the variance. Within psychological capital, optimism, hope, and self-efficacy significantly predicted flourishing, explaining 59.4% of its variance; resilience, while correlated, was not a significant predictor. Notably, psychological capital moderated the relationship between extraversion and flourishing: individuals high in extraversion and psychological capital reported enhanced flourishing. From a management perspective, interventions that strengthen psychological capital may be especially beneficial for employees high in extraversion, potentially fostering greater well-being, work efficiency, and productivity.